Modulated high frequency excitation approach to nonlinear ultrasonic NDT. (28th April 2019) - Carcione, A.; Blanloeuil, P.; Rose, L.R.F.; Wang, Chun H.; Veidt, M.
Abstract: A novel approach for nonlinear ultrasonics is presented which relies on an amplitude modulated high-frequency excitation, as distinct from the conventional vibro-acoustic approach based on a low-frequency pumping wave in combination with a high-frequency probing wave. This amplitude modulated excitation contains three frequencies that interact in the presence of nonlinearity and transfers energy to frequencies not part of the original input. This effect can be exploited to detect and quantify damage-induced nonlinearity. This novel method is demonstrated experimentally for three distinct contact conditions, utilising different types of transducer and excitation signals of various amplitudes and frequencies. The performance is compared with the conventional vibro-acoustic technique. It is shown that the new technique has comparable performance to existing methods. Specialized measurement system design with superb sensitivity is also demonstrated. Unlike conventional cross-modulation based nonlinear ultrasonic techniques, this new method does not require two separate excitation sources. This represents a significant practical advantage which will greatly facilitate the implementation of nonlinear ultrasonic methods for a wide range of applications.